2020
DOI: 10.1575/1912/26071
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Atlantic Water in the Arctic Ocean using the Arctic Subpolar Gyre State Estimate and observations

Abstract: The Atlantic Water (AW) Layer in the Arctic Subpolar gyre sTate Estimate (ASTE), a regional, medium-resolution coupled ocean-sea ice state estimate, is analyzed for the first time using bounding isopycnals. A surge of AW, marked by rapid increases in mean AW Layer potential temperature and AW Layer thickness, begins two years into the state estimate (2004) and traverses the Arctic Ocean along boundary current pathways at approximately 2 cm/s. The surge also alters AW flow direction and speed including a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…After 2012, the model showed that dense AW progressively shoaled along the East Siberian Sea slope (Figure 9) until reaching the Mendeleev Ridge by the end of 2017 (Figure 7g). This is in agreement with a previous model‐based study that described the thickening and warming of the AW layer as far as the Mendeleev Ridge in 2010–2017, although no change had been found in the AW layer upper boundary (Grabon et al., 2021). Here, the PSY4 simulations showed that the AW shoaling was accompanied by a weakening of the halocline.…”
Section: Discussionsupporting
confidence: 93%
“…After 2012, the model showed that dense AW progressively shoaled along the East Siberian Sea slope (Figure 9) until reaching the Mendeleev Ridge by the end of 2017 (Figure 7g). This is in agreement with a previous model‐based study that described the thickening and warming of the AW layer as far as the Mendeleev Ridge in 2010–2017, although no change had been found in the AW layer upper boundary (Grabon et al., 2021). Here, the PSY4 simulations showed that the AW shoaling was accompanied by a weakening of the halocline.…”
Section: Discussionsupporting
confidence: 93%
“…Arctic Circumpolar Current: In the Laptev Sea it is thought that the circumpolar circulation of AW splits at ∼145 • E, with a fraction returning to Fram Strait along the Lomonosov Ridge (Rudels, 2015) and the remainder continuing along the basin's rim into the Western Arctic, although the exact partitioning is not well constrained. In the Western Arctic it is typically assumed that the AW continues to circulate cyclonically along the basin boundary, although both ASTE R1 (Grabon, 2020) and a modeling effort informed by observed radionuclide distributions (Karcher et al, 2012) suggest a weak anticyclonic circulation during the last decade. Recent work analyzing all available current meters (updated from Baumann et al (2018)) has yielded velocity probability distributions for the Arctic region.…”
Section: Known Issues and Future Directionsmentioning
confidence: 99%
“…All rights reserved. data comparisons (e.g., Grabon, 2020), the interpolation introduces additional information that was not strictly solved for by the model. An alternate approach is to vary the salinity bounds to gauge the sensitivity of the heat content within this watermass to the vertical discretization in the model.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In the Laptev Sea it is thought that the circumpolar circulation of AW splits at ∼145°E, with a fraction returning to Fram Strait along the Lomonosov Ridge (Rudels, 2015) and the remainder continuing along the basin's rim into the Western Arctic, although the exact partitioning is not well constrained. In the Western Arctic it is typically assumed that the AW continues to circulate cyclonically along the basin boundary, although both ASTE_R1 (Grabon, 2020) and a modeling effort informed by observed radionuclide distributions (Karcher et al, 2012) suggest a weak anticyclonic circulation during the last decade. Recent work analyzing all available current meters (updated from Baumann et al, 2018) has yielded velocity probability distributions for the Arctic region.…”
Section: Arctic Circumpolar Currentmentioning
confidence: 99%